Work Engagement to Moderate Servant Leadership and Knowledge Sharing on Teachers' Innovative Work Behavior - Hendro Prasetyono; Ira Pratiwi Ramdayana; Iin Asikin; Nurdin Nurdin; Saring Saring (Jurnal Pemberdayaan Masyarakat, 2025)
This research aims to determine whether work engagement can moderate the relationship between servant leadership and knowledge sharing in influencing innovative work behavior among high school teachers. The research employs a quantitative approach, utilizing survey methods to collect data. Respondents were 158 high school teachers in West Java Province, Indonesia. The sampling technique is simple random sampling. The questionnaire is compiled from the development of dimensions for each variable, using a Likert scale with five answer choices. The data analysis technique uses path analysis. The results of work engagement research can moderate the relationship between servant leadership and knowledge sharing, both partially and simultaneously, in relation to innovative work behavior. The results of this research have implications for school principals on how to increase teacher work engagement through training or supervision, which warrants further investigation. These results contribute to the theory that work engagement can strengthen the influence of servant leadership and knowledge sharing on the innovative work behavior of high school teachers. A limitation of this research is that it was conducted only on teachers in West Java Province. The results of this research contribute to the development of an innovative work behavior theory, suggesting that the influence of servant leadership and knowledge sharing can be strengthened when moderated by work engagement.